Evaluation of the hospital morbidity profile of patients with Diabetes mellitus in the state of Maranhão - Cardoso, Alcilene Pereira; Oliveira, Kelly Beatriz Vieira de (Research, Society and Development, 2023)
Diabetes has been a significant public health problem globally, regardless of the country’s level of development. Its impact is felt in terms of the number of people affected, disability, premature mortality and costs associated with managing and treating its complications. The disease is the fourth leading cause of death worldwide and one of the most common chronic conditions. Given the range of progressively aggravating physiological problems associated with diabetes, it has become crucial to look at factors that may be linked to these conditions. In this context, the study in question was carried out with the objective of evaluating the particularities of patients who resort to the public health network for the treatment of Diabetes Mellitus. Specifically, the study analyzed the profile of patients who were hospitalized due to Diabetes Mellitus (I and II) in the state of Maranhão, Brazil. The research was carried out through a documentary evaluation study, using public data from the statistical tools of the DATASUS network via Tabnet/SIH/SUS. The study population consisted of the state of Maranhão, which has a total of 6.851 million inhabitants, which were stratified to provide the necessary data for the analysis and evaluation of characteristics that may be associated with the worsening of diabetes. Study results demonstrated an increasing trend in disease severity with age and a higher incidence of decompensation in women. These findings reinforce the need for more targeted and personalized public health interventions, taking into account factors such as age and gender.